2005
DOI: 10.1093/ecam/neh081
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SARS‐CoV 3C‐like Protease Activity by Theaflavin‐3,3′‐digallate (TF3)

Abstract: SARS-CoV is the causative agent of severe acute respiratory syndrome (SARS). The virally encoded 3C-like protease (3CLPro) has been presumed critical for the viral replication of SARS-CoV in infected host cells. In this study, we screened a natural product library consisting of 720 compounds for inhibitory activity against 3CLPro. Two compounds in the library were found to be inhibitive: tannic acid (IC50 = 3 µM) and 3-isotheaflavin-3-gallate (TF2B) (IC50 = 7 µM). These two compounds belong to a group of natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
203
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 213 publications
(224 citation statements)
references
References 20 publications
5
203
0
5
Order By: Relevance
“…In addition to small molecules from chemical libraries, some research groups have turned to natural plant extracts such as Chinese herbs. Two research groups individually claimed that tannic acid, 3-isotheaflavin-3-gallate and theaflavin-3,3'-digallate from black tea and one plant-derived phenolic compound, hesperetin, are SARS-CoV M pro inhibitors [95,96].…”
Section: High-throughput Screeningmentioning
confidence: 99%
“…In addition to small molecules from chemical libraries, some research groups have turned to natural plant extracts such as Chinese herbs. Two research groups individually claimed that tannic acid, 3-isotheaflavin-3-gallate and theaflavin-3,3'-digallate from black tea and one plant-derived phenolic compound, hesperetin, are SARS-CoV M pro inhibitors [95,96].…”
Section: High-throughput Screeningmentioning
confidence: 99%
“…Therefore, it may be suggested that polyphenols (as supplements or in polyphenol-enriched diets) offer potential health benefits for HIV patients or could be promising candidates for the development of topical microbicides to reduce sexual HIV-1 transmission. Furthermore, antiviral activity of polyphenols has also been demonstrated for the severe acute respiratory syndrome-coronavirus infection [136] and herpes simplex virus (HSV-1 and HSV-2) infection [137]. However, increasing the local or systemic uptake of polyphenols might not be without risks.…”
Section: Enhancing the Cellular Antioxidant Defense As An Antiviral Smentioning
confidence: 99%
“…Through screening from a natural product library consisting of 720 compounds, Chen et al obtained two compounds, namely, tannic acid (IC 50 = 3 µM) and 3-isotheaflavin-3-gallate (TF2B) (IC 50 = 7 µM) as potent inhibitors of SARS 3CL pro [50]. These two compounds belong to a group of natural polyphenols in tea, and therefore Chen et al further investigated the 3CL pro inhibitory activities of the extracts from different types of tea including green tea, oolong tea, Puer tea, and black tea.…”
Section: A From High Throughput Screeningmentioning
confidence: 99%